PENATALAKSANAAN KETOASIDOSIS DIABETIK (KAD) - Gotera, Wira; Agung Budiyasa, Dewa Gde (journal of internal medicine; Vol. 11, No. 2 Mei 2010, 2012)
Diabetic Ketoasidosis (DKA) is metabolic disturbance disorder that be signed by trias hyperglycemia, acidosis, and ketosis, which one of very serious acute metabolic complication of diabetes mellitus. In Indonesia the incidence was not so high compare than the western countries, but the mortality is still high. In young age the mortality can be prevented by early diagnosis, rational and prompt treatment according to it!s pathophysiology. Succesfull of DKA treatment needs correction of dehidration, hyperglycemia, acidosis, and electrolyte disturbance, identiÞ cation of comorbid precipitation factor, and the most important one was continue monitoring. The treatment were adequate of ß uid therapy, sufÞ cient insulin theraphy, therapy of potassium, bicarbonate, phosphat, magnesium, hyperchloremic condition, and antibiotic administration according to indication. The important one was also awarness for therapy complications so that the therapy not to make worsening condition of the patients.
Keywords: diabetic, ketoacidosis, management